2016
DOI: 10.1111/cjag.12120
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Market Intervention on Quota Mobility: The Case of the Ontario Dairy Industry

Abstract: We examine the relationship between farm-level scale efficiency and quota purchases in the Ontario dairy quota market before and after the implementation of a progressive transfer assessment policy and a price cap policy. We find that scale efficiency has a positive effect on net quota purchases and that the two regulations slowed down this effect. The largest deterrent in the movement of quota from less efficient to more efficient producers occurred after the implementation of the capital asset pricing policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…An unregulated system where farmers are free to trade their quotas favors efficiency. Elskamp and Hailu () show empirically that policies capping quota prices in the Ontario dairy industry slowed down quota transaction between inefficient and efficient dairy farms.…”
Section: Regional Differences In Farm Sizementioning
confidence: 99%
“…An unregulated system where farmers are free to trade their quotas favors efficiency. Elskamp and Hailu () show empirically that policies capping quota prices in the Ontario dairy industry slowed down quota transaction between inefficient and efficient dairy farms.…”
Section: Regional Differences In Farm Sizementioning
confidence: 99%
“…5 While the dairy quota price cap achieved the objective of curtailing the rapid increase in quota values, it caused inefficiency in the quota market (Cairns and Meilke 2012), as demand vastly exceeded supply. In an unrestricted quota exchange, Elskamp and Hailu (2017) found that quota tended to be transferred from less efficient to more efficient producers, but the implementation of the price cap slowed this transfer and compromised the ability of the quota auction to allocate quota to the most efficient producers. Following the implementation of the cap, very little quota was made available on the market as many producers were unwilling to sell at the lower price, which meant that producers seeking to expand their dairy operations were largely unable to do so.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bids were restricted to 10% of a producer's existing quota holdings, which made it very difficult for dairy producers to make any substantial increases to the size of their operations. As noted by Elskamp and Hailu (2017), this was concerning due to the resulting inability for producers to acquire the quota needed for facilities that were expanded just prior to the implementation of the price cap, as well as the likelihood that the more efficient producers that would have expanded to take advantage of economies of scale would likely be forced to put expansion on hold.…”
Section: Introductionmentioning
confidence: 99%
“…Sauer (2010) shows that deregulating the quota trading system in Denmark has led to efficiency gains. Elskamp and Hailu (2017) show that regulations embedded in a quota transfer scheme in Ontario slow the process of concentrating the quota among the more efficient producers.…”
Section: Introductionmentioning
confidence: 99%